FEATURES OF STATE REGULATION INDUSTRY IN RUSSIA - Natalia Viktorovna Borovikova (Современная наука и инновации)
Industrial policy - a set of measures of state regulation of business entities (companies, corporations, entrepreneurs, etc.), as well as some aspects of the activities related to the acquisition of factors of production, organization of production, distribution and sale of goods and services in all phases of the life cycle of the entity and the life cycle of its products.